Damage-associated responses of the host contribute to defence against cyst nematodes but not root-knot nematodes - Shah, Syed Jehangir (Journal of experimental botany, 2017)
© The Author 2017. Published by Oxford University Press on behalf of the Society for Experimental Biology.